Nematodes in a polar desert reveal the relative role of biotic interactions in the coexistence of soil animals - Caruso, Tancredi; Hogg, Ian D.; Nielsen, Uffe N.; Bottos, Eric M.; Lee, Charles K.; Hopkins, David W.; Cary, S. Craig; Barrett, John E.; Green, T.G. Allan; Storey, Bryan C.; Wall, Diana H.; Adams, Byron J. (Communications Biology, 2019)
Abiotic factors are major determinants of soil animal distributions and their dominant role is pronounced in extreme ecosystems, with biotic interactions seemingly playing a minor role. We modelled co-occurrence and distribution of the three nematode species that dominate the soil food web of the McMurdo Dry Valleys (Antarctica). Abiotic factors, other biotic groups, and autocorrelation all contributed to structuring nematode species distributions. However, after removing their effects, we found that the presence of the most abundant nematode species greatly, and negatively, affected the probability of detecting one of the other two species. We observed similar patterns in relative abundances for two out of three pairs of species. Harsh abiotic conditions alone are insufficient to explain contemporary nematode distributions whereas the role of negative biotic interactions has been largely underestimated in soil. The future challenge is to understand how the effects of global change on biotic interactions will alter species coexistence.